PENGUSAHAAN NIPAH DAN PERMASALAHANNYA - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
A general investigation of thatch palm utilization in South Sumatra, Lampung and West Kalimantan had been conducted in 1991. The resuti and the very limited publications available show that the accurate area, distriburion and potential of thatch palm forests in Indonesia are not known yet. The traditional use of thatch palm leaves for making roof has been know for a long time but it is still without any improvement. while the utilization of the palm for various commercial products is new and, therefore, many of its aspects have not been known yet. It is now realized that all of the palm portions such. as leaf, stem, fruit and juice can be used for certain products with relatively high economical values.lt is noticed that in business of thatch palm utilization industry in Indonesia, several constraisus are commonly faced such as the lack of data of the palm area, distribution and potential, the unclear institution responsible for the commodity, the long procedure of gelling the permit for managing lhatch palm, the difficult condition of thatch palm field and lack of infrastructure, the lack of skilled labor, technology, environmental information, the lack of socio- economical analysis, the difficulty in getting fund, and the lack of real support from the government.Further research on various aspects of thatch palm utilization and development are necessary in order to provide scientific information to be used by interested parties so that the rote of the commodity in improving the general life of local community and increasing government earning can be realized.